2009
DOI: 10.1111/j.1471-0374.2009.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Brain circulation’ and transnational knowledge networks: studying long‐term effects of academic mobility to Germany, 1954–2000

Abstract: ‘Brain circulation’ has become a buzzword for describing the increasingly networked character of highly skilled migration. In this article, the concept is linked to academics' work on circular mobility to explore the long‐term effects of their research stays in Germany during the second half of the twentieth century. Based on original survey data on more than 1800 former visiting academics from 93 countries, it is argued that this type of brain circulation launched a cumulative process of subsequent academic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(145 citation statements)
references
References 39 publications
2
129
0
14
Order By: Relevance
“…In both cases there is evidence of a statistically significant relationship between the network and the mobility variables 4 , suggesting that scientists with previous long term mobility are relatively more likely to have foreign organisations among their main knowledge contacts. These results are consistent with previous research that has identified a relationship between international mobility and network building (Turpin et al, 2008;Jöns, 2009). However, the data also show that although long-term mobility appears to increase the propensity to establish international knowledge networks, international networking is a relatively generalised phenomenon, even among non mobile scientists.…”
Section: N=353supporting
confidence: 83%
See 2 more Smart Citations
“…In both cases there is evidence of a statistically significant relationship between the network and the mobility variables 4 , suggesting that scientists with previous long term mobility are relatively more likely to have foreign organisations among their main knowledge contacts. These results are consistent with previous research that has identified a relationship between international mobility and network building (Turpin et al, 2008;Jöns, 2009). However, the data also show that although long-term mobility appears to increase the propensity to establish international knowledge networks, international networking is a relatively generalised phenomenon, even among non mobile scientists.…”
Section: N=353supporting
confidence: 83%
“…Differences between scientific fields in terms of mobility (Canibano et al, 2008) and in terms of the presence of collaborative networks and nature of the relationships established (Jöns, 2009;Wagner, 2005), have been described in the literature. Differences are particularly evident between exact and natural sciences (where collaborations tend to assume the form of co-publications and scientific consulting); and social sciences and humanities (where copublications are less dominant).…”
Section: Data and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that long-term processes, for example, changes of cultural meanings and societal behaviors resulting from new information, and the influence of different ways of life introduced by returning migrants (long and shortterm returns), play a crucial role in such knowledge flows but are not well quantifiable. Jöns (2009) has shown this effect in the context of transnational knowledge networks through the example of circular academic mobility to Germany.…”
Section: Integration Between Structural Forces and Individual Abilitimentioning
confidence: 99%
“…The host country gains human capital, both the home and host society economies experience a positive impact resulting from circulatory knowledge flows, and the migrants themselves also benefit (Salt & Findlay, 1989;Findlay, 1995;Jöns, 2009;Lee & Kim, 2010). The country of destination may also see increased tax income.…”
Section: Integration Between Structural Forces and Individual Abilitimentioning
confidence: 99%